Demographic risk factors of pro-inflammatory diet: a narrative review - Pourmontaseri, Hossein; Khanmohammadi, Shaghayegh (Frontiers in Nutrition, 2024)
While natural inflammation is a known beneficial mechanism, pro-inflammatory nutrients develop chronic inflammation. The energy-adjusted dietary inflammatory index (E-DII) revealed positive associations with chronic inflammatory-related diseases. However, more evidence about the demographic risk factors for high E-DII is needed. Therefore, the present study reviewed the high-risk groups of people for high E-DII scores. Men had higher E-DII than women worldwide, which would be explained by the craving for energy induced by stress and higher physical activity. However, in some societies, women had higher consumption of a pro-inflammatory diet, which would be induced by compulsive eating and craving for more sweat and carbohydrates during menstruation and among women with premenopausal syndrome. The pro-inflammatory diets were more common among elders in southern America, East Asia, and Arab countries, while some other studies had controversies. The development of unhealthy nutrients, such as fast foods and Western dietary patterns enriched with a proinflammatory diet, increased youth's E-DII and decreased the healthy eating index among older people. Also, smokers and alcoholics attended to intake higher E-DII, which should be investigated in further studies. Black people consumed the most pro-inflammatory diets compared with White people, especially in pregnant women. Education had a negative association with E-DII, while socioeconomic status was positively associated with a proinflammatory diet. Therefore, E-DII consumption had no relation to access to healthy foods but is more associated with knowledge and cultural dietary habits. Moreover, further nutritional interventions are required to educate the vulnerable populations and also provide better availability of healthy food enriched with anti-inflammatory nutrients in the future.